(untitled) (South East Asia Journal of Public Health, 2016)
During the past decade, academics, bloggers, media practitioners and civil society groups in Bangladesh have criticized the tobacco industry for bringing about negative effects on societal health, environment, agriculture and education. Moreover, several newspaper reports have suggested these companies to be corrupt engaging in bribery, breaking of government regulations and laundering of money. In reply to these criticisms, tobacco firms have propagated discourses through the art of rhetoric in the public domain and initiated corporate social responsibility (CSR) activities to project themselves as caring and responsible entities. In light of this, the paper studied and evaluated the discourses on governance, transparency and responsibility as well as the CSR undertakings of the leading tobacco firms in the country British American Tobacco Bangladesh (BATB), Dhaka Tobacco Industries (DTI), Akij Group and Nasir Tobacco Industries. We searched related electronic and/or printed documents using a snowball technique and discourse analysis approach to review the documents. Findings indicated that tobacco companies highlighted in their communication materials (websites, annual reports, news releases, brochures, etc.) the following: ethical business practices, social responsibility, sound corporate governance, quality management and economic success. They likewise made it a point to associate themselves with important events in the nations history, particularly the 1971 Liberation War. More importantly, these companies conducted CSR activities in the areas stakeholders criticized them the most environmental protection (afforestation, biodiversity conservation and renewable energy), health (hospitals), education (primary education, youth development and scholarships) and agriculture (extension services). In so doing, these firms have managed to divert criticisms and instead, create a buzz regarding their social initiatives and governance practices. In this sense, the tobacco industry had succeeded in placing itself at a high moral ground in the country. In this light, it is recommended that further studies should be conducted regarding the CSR projects of tobacco companies in the country analyzing whether these fit to the relevant criteria and acceptable standards of a CSR. South East Asia Journal of Public Health Vol.5(2) 2015: 13-22